2017
DOI: 10.1007/s13346-017-0422-3
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of polycaprolactone nanoparticles via supercritical carbon dioxide extraction of emulsions

Abstract: Polycaprolactone (PCL) nanoparticles were produced via supercritical fluid extraction of emulsions (SFEE) using supercritical carbon dioxide (scCO). The efficiency of the scCO extraction was investigated and compared to that of solvent extraction at atmospheric pressure. The effects of process parameters including polymer concentration (0.6-10% w/w in acetone), surfactant concentration (0.07 and 0.14% w/w) and polymer-to-surfactant weight ratio (1:1-16:1 w/w) on the particle size and surface morphology were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 35 publications
3
18
0
1
Order By: Relevance
“…A slightly different diameter (167.3 nm) and polydispersity index (0.114) were obtained for the PUA‐NPs@PTX with a zeta potential of −29.2 mV ( Figure a,b). The surface of the nanoparticles carried a negative charge, which may be due to the carbonyl group possessed by the PUA, as reported previously . Obviously, the size of the PUA‐NPs@PTX was slightly larger than the blank NPs.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…A slightly different diameter (167.3 nm) and polydispersity index (0.114) were obtained for the PUA‐NPs@PTX with a zeta potential of −29.2 mV ( Figure a,b). The surface of the nanoparticles carried a negative charge, which may be due to the carbonyl group possessed by the PUA, as reported previously . Obviously, the size of the PUA‐NPs@PTX was slightly larger than the blank NPs.…”
Section: Resultssupporting
confidence: 65%
“…The surface of the nanoparticles carried a negative charge, which may be due to the carbonyl group possessed by the PUA, as reported previously. [24] Obviously, the size of the PUA-NPs@PTX was slightly larger than the blank NPs. The size of PUA-NPs and PUA-NPs@PTX was further confirmed by transmission electron microscope (TEM) imaging, as well as the spherical-like morphology of the nanoparticles (Figure 2c; Figure S4b, Supporting Information).…”
Section: Preparation and Characterization Of Pua-nps And Pua-nps@ptxmentioning
confidence: 96%
“…Therefore, formulae F3, F6, F5, and F2 were Upon studying the effect of stabilizer (Cremophor EL) concentration (0%, 2%, and 4% w/w) on the particle size, it was observed that increasing the concentration of stabilizer resulted in decreasing the particle size significantly (p < 0.0001), as illustrated in Figure 1b. This might be reckoned to the presence of large number of surfactant molecules at the interfacial layer, which resulted in decreasing the surface tension and therefore promoting the formation of smaller droplets [49][50][51].…”
Section: In-vitro Release Studymentioning
confidence: 99%
“…These features lead to a significant reduction of the particle size on applying both PVA and Tween 80 surfactants. The absence of surfactant at the solvent-water interface results in coalescence and an increase in size of the formed particles [4,32].…”
Section: Nature Of the Surfactantmentioning
confidence: 99%
“…They can cause controlled release of drugs over a long time in the body and also protect them from enzymatic degradation [3]. Recently, polymeric biocompatible and biodegradable NPs such as poly-lactic-co-glycolic acid, poly-lactic acid, and polycaprolactone (PCL) as synthetic polymers and natural polymers such as chitosan and hyaluronan have been considered as drug delivery systems (DDSs) [4]. Drug release modes such as delayed, triggered, and prolonged could be modified by these polymers [5][6][7].…”
Section: Introductionmentioning
confidence: 99%